Literature Study of Factors Causing Fraud in Public & Private Sector Companies - Amir Nur Hidayat (Robust: Research of Business and Economics Studies, 2022)
This study describes the factors that cause fraud in Indonesia, both from public and non-public sector organizations. The research carried out is a literature review research sourced from articles that follow the research topic for further analysis. The research method used is a descriptive qualitative method by taking data from literacy studies on research on fraud in various entities in Indonesia. The results of this study are expected to be used as an initial method of fraud detection and provide input and additional insight to all parties, including company management, auditors, and users of financial statements, about the factors that cause fraud in public and private sector companies.